2013
DOI: 10.1098/rsif.2013.0464
|View full text |Cite
|
Sign up to set email alerts
|

Label-free Raman monitoring of extracellular matrix formation in three-dimensional polymeric scaffolds

Abstract: Monitoring extracellular matrix (ECM) components is one of the key methods used to determine tissue quality in three-dimensional scaffolds for regenerative medicine and clinical purposes. Raman spectroscopy can be used for noninvasive sensing of cellular and ECM biochemistry. We have investigated the use of conventional (confocal and semiconfocal) Raman microspectroscopy and fibre-optic Raman spectroscopy for in vitro monitoring of ECM formation in three-dimensional poly(ethylene oxide terephthalate)-poly(buty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 54 publications
2
37
0
Order By: Relevance
“…The authors reported the use of Raman spectroscopy to quantify and image collagen, GAG and water distributions in the engineered constructs (Figure 7). Kunstar et al 139 reported on the use of Raman for monitoring extracellular matrix components in tissue engineered cartilage in addition to biochemical and histological analysis. Poly (ethylene oxide terephthalate)/poly (butylene terephthalate) scaffolds were seeded with primary bovine chondrocytes and evaluated at 7 and 21 days of culture.…”
Section: Raman Spectroscopy and Tissue Engineeringmentioning
confidence: 99%
“…The authors reported the use of Raman spectroscopy to quantify and image collagen, GAG and water distributions in the engineered constructs (Figure 7). Kunstar et al 139 reported on the use of Raman for monitoring extracellular matrix components in tissue engineered cartilage in addition to biochemical and histological analysis. Poly (ethylene oxide terephthalate)/poly (butylene terephthalate) scaffolds were seeded with primary bovine chondrocytes and evaluated at 7 and 21 days of culture.…”
Section: Raman Spectroscopy and Tissue Engineeringmentioning
confidence: 99%
“…At present, optical methods of research have become widely used for the study of bioobjects: backward scattering spectroscopy [4], microscopic analysis [5,6], and Raman spectroscopy [7,8]. Raman spectroscopy has certain advantages over other methods.…”
Section: Physbiosymp17mentioning
confidence: 99%
“…The authors of the articles [9,10], conducted studies of the structure of the synovial fluid and evaluated the content of their protein components.…”
Section: Physbiosymp17mentioning
confidence: 99%
“…Careful selection of suitable laser wavelengths and laser intensity can eliminate cell damage allowing for the study of cells without inadvertently changing their phenotype or behavior caused by photo damage [191][192][193]. Raman spectral studies have been performed for structural analysis of ECM components such as collagen [194] and proteoglycans [189,195]. Raman peaks at distinct wavelengths exist, for example, for different types of carbon-carbon bonds, amide, carboxyl, sulfhydryl, and phenol groups [120].…”
Section: Raman Microspectroscopymentioning
confidence: 99%
“…Raman microspectroscopy is a label-free spectroscopic technique, which does not require special sample preparation and can be used for non-invasive characterization of cell and tissue biochemistry [189,190]. Careful selection of suitable laser wavelengths and laser intensity can eliminate cell damage allowing for the study of cells without inadvertently changing their phenotype or behavior caused by photo damage [191][192][193].…”
Section: Raman Microspectroscopymentioning
confidence: 99%